THE USE OF REQUEST STRATEGIES OF INDUSTRIAL ENGINEERING STUDENTS - Yoga Prihatin; Nur Aflahatun (University of Kuningan, 2020)
The aim of this study is to investigate the types of the request strategy used by Industrial Engineering students as EFL learners. Using qualitative data, this study discusses the use of request strategy in case-based teaching of foreign languages. The participants of the study are 37 Industrial engineering students who learnt English in the second semester. The testing instruments used were discourse completion task. For this aim, a discourse completion test was used to generate data related to the request strategies by each group. Selection of request situation in discourse completion test was based on three social factors of relative social distance, power, and rank of imposition. The participants’ responses were analyzed according to the classifications of request strategy by Blum-Kulka & Olshtain. The case study findings indicate that 57% of Industrial Engineering students’ responses mostly use conventional indirect strategies, 29.2 % responses are direct strategies, and 13 % responses belong to non-conventional indirect strategies. 49.7 % responses belong to query preparatory. 17.8 % responses are identified as explicit performatives, 10.3 % responses categorized as want statements, 9.2 % responses classified as strong hints, 6.5 % responses grouped as mild hints, 4.9 % responses recognized as suggestive formulas, and 1.6 % responses indicated as mood derivable. The indirectness is greatly influenced by students’ cultural background, which belong to high-context culture. People in high context culture refer to the value cultures placing on indirect communication. A message is understood with a great deal of gesture, facial expressions, tone of voice, eye contact, body language, posture, and other ways people can communicate without using language. The findings of this study may set pedagogical implications for teachers, and learners of EFL therefore conducting a further field investigation is recommended to have in depth exploration about request strategies made by EFL Learners.